If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 3(3x + 4) = 156 Reorder the terms: 3x + 3(4 + 3x) = 156 3x + (4 * 3 + 3x * 3) = 156 3x + (12 + 9x) = 156 Reorder the terms: 12 + 3x + 9x = 156 Combine like terms: 3x + 9x = 12x 12 + 12x = 156 Solving 12 + 12x = 156 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 12x = 156 + -12 Combine like terms: 12 + -12 = 0 0 + 12x = 156 + -12 12x = 156 + -12 Combine like terms: 156 + -12 = 144 12x = 144 Divide each side by '12'. x = 12 Simplifying x = 12
| 37=25-2/3x | | 8x+7=8x-x | | 10-6n=2-n | | 5x+78=34-3x | | 5/9×45-32 | | 5.5x+348.25=1000 | | 2.50r=90 | | (5x+x)-(2.2x+8)= | | 6z+z=6z-2 | | 2(x+6)+7(3x-4)= | | 5(8-9m)-4=-9 | | 3.4*c-1.7=6.8 | | 3k-2+4k=-23 | | 33=3x-9 | | 5x+78=48+3x | | X+-2=10 | | x+3(-2)=1 | | 5x-3/x-1=3/2 | | 53+8x-4=90 | | 6+3x-2x=9 | | f(n)=2(3) | | .25x+78=48-3x | | 48/9=72/h | | x-1.4=6.0 | | -3y-4y-12y= | | 3x+9-7(x+1)=4x+7 | | (15x)/5 | | 15x-7x=48 | | .25x-5x=2x+43 | | -4i-6j= | | (6x-18)(3x+12)=0 | | -6(4p+3)-34=4(2p+3) |